2020
DOI: 10.1002/cne.24972
|View full text |Cite
|
Sign up to set email alerts
|

Brain gyrification in wild and domestic canids: Has domestication changed the gyrification index in domestic dogs?

Abstract: Over the last 15 years, research on canid cognition has revealed that domestic dogs possess a surprising array of complex sociocognitive skills pointing to the possibility that the domestication process might have uniquely altered their brains; however, we know very little about how evolutionary processes (natural or artificial) might have modified underlying neural structure to support species‐specific behaviors. Evaluating the degree of cortical folding (i.e., gyrification) within canids may prove useful, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 90 publications
(149 reference statements)
1
21
0
Order By: Relevance
“…The average cortical gyrencephalic index measured in the African wild dog was 1.76 ( SD = 0.03). Recent allometric analyses in the Carnivora revealed a strong hypoallometric relationship between brain mass and GI (Grewal et al, 2020). Here we reproduced a subset of the Carnivora data from Grewal et al (2020) as shown in Figure 9 and demonstrate that the mean GI for the African wild dog is very close to what would be predicted for a carnivore with a brain mass of around 160 g (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average cortical gyrencephalic index measured in the African wild dog was 1.76 ( SD = 0.03). Recent allometric analyses in the Carnivora revealed a strong hypoallometric relationship between brain mass and GI (Grewal et al, 2020). Here we reproduced a subset of the Carnivora data from Grewal et al (2020) as shown in Figure 9 and demonstrate that the mean GI for the African wild dog is very close to what would be predicted for a carnivore with a brain mass of around 160 g (Figure 9).…”
Section: Resultsmentioning
confidence: 99%
“…One example of this is the finding that volumetric changes in the size of the lateral cerebellar hemispheres (independent of cerebellar size) are correlated with measures of domain‐general cognition in primates (Smaers, Turner, Gomez‐Robles, & Sherwood, 2018). Similarly, Grewal et al (2020) point out that local gyrification differences (in the Canidae) of potential functional significance may be masked by more global differences in cortical folding and thus, in order to explain the behavioral specializations exhibited by the African wild dog, a more in‐depth analysis of structural‐functional differences is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, post-mortem MRI data are important because they share common signal forming mechanisms with in vivo MRI and a common tissue state with microscopy, providing a framework for investigation across multiple spatial scales. Postmortem MRI facilitates comparative anatomy investigations in species that are not traditionally accessible for in-vivo imaging (Berns et al, 2015;Bhagwandin, Haagensen, & Manger, 2017;Grewal et al, 2020;Heuer et al, 2019), including extinct species (Berns & Ashwell, 2017). Long post-mortem scans provide the opportunity to push the boundaries of spatial resolution, providing whole human brain coverage reaching voxel sizes of 100-500 μm (Edlow et al, 2019;Foxley et al, 2016;Fritz et al, 2019;Weigel et al, 2021), edging closer to microscopy techniques but benefitting from compatibility with in-vivo imaging.…”
Section: Introductionmentioning
confidence: 99%